2014 Australasian Universities Power Engineering Conference (AUPEC) 2014
DOI: 10.1109/aupec.2014.6966551
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive experimental study on the stabilization of active magnetic bearing system

Abstract: This paper investigates performance of various controllers on the stabilization of active magnetic bearing system (AMBs). Firstly, since AMBs are inherently open-loop unstable, closed-loop system identification is adopted in order to obtain the model of the system under study. Next, based on the obtained model, Linear Quadratic Gaussian (LQG), PD-like Fuzzy Controller (PD-FLC), PID-like Fuzzy Controller (PID-FLC) andController are designed. These controllers are then coded in C and implemented in real time on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A more advanced (and more expensive) option consists of using a DSP instead of a general-purpose MCU. This is reported in a number of works [12][13][14][15][16][17][18][19][20].…”
Section: Introduction 1pid Regulators In Contemporary Technologiesmentioning
confidence: 70%
See 1 more Smart Citation
“…A more advanced (and more expensive) option consists of using a DSP instead of a general-purpose MCU. This is reported in a number of works [12][13][14][15][16][17][18][19][20].…”
Section: Introduction 1pid Regulators In Contemporary Technologiesmentioning
confidence: 70%
“…Nevertheless, some fast-controlled objects require sampling periods as short as tens of microseconds. In particular, it applies to the stabilization of magnetic bearings [11,16,17] and precise motion control [21]. In [21], a PID regulator is used to control the operation of insect-size robots.…”
Section: Introduction 1pid Regulators In Contemporary Technologiesmentioning
confidence: 99%
“…Several forms of fuzzy controllers can be found in the literature [19][20][21][22][23][24][25]. It should be clear to the readers that the focus of this paper is on so-called direct action fuzzy controller.…”
Section: Pid-type Fuzzy Logic Controllersmentioning
confidence: 99%
“…Hence, the use of control techniques for the balance and control of the AMB system is crucial. A significant amount of research has been reported in the recent decades by Mushi et al (2011) and Noshadi et al (2014) to stabilize and regulate the AMB system.…”
Section: Introductionmentioning
confidence: 99%